Economic growth and environmental policy : a theoretical approach - Hettich, Frank; Oates, Wallace E.; Folmer, Henk. (Cheltenham, UK ; Northampton, MA, USA : E. Elgar Pub., 2000)
This book uses dynamic modeling to study the interaction between economic growth, environmental policy and tax reform.
Includes index.
Includes bibliographical references (p. 235-254).
osc 06/09/2016, ijb 09/04/2019
Loan
Keywords: Economic development; Environmental policy